2021
DOI: 10.1212/wnl.0000000000012060
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of Cardiac Innervation Scintigraphy for Mild Cognitive Impairment With Lewy Bodies

Abstract: ObjectiveTo provide evidence that cardiac I-123-metaiodobenzylguanidine sympathetic innervation imaging (MIBG) scintigraphy differentiates probable mild cognitive impairment with Lewy bodies (MCI-LB) from mild cognitive impairment due to Alzheimer disease (MCI-AD), we scanned patients with MCI and obtained consensus clinical diagnoses of their MCI subtype. We also performed baseline FP-CIT scans to compare the accuracy of MIBG and FP-CIT.MethodsWe conducted a prospective cohort study into the accuracy of cardi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 32 publications
(48 citation statements)
references
References 23 publications
(49 reference statements)
1
46
0
1
Order By: Relevance
“…Cardiac scintigraphy with MIBG is a biomarker for DLB 29 and in this cohort we recently reported that MIBG also had diagnostic accuracy in distinguishing MCI-LB from MCI-AD, 12 providing further evidence that autonomic nervous system involvement is present at the MCI stage. However, we did not find any clear association between cardiac denervation assessed with MIBG imaging and autonomic symptoms within MCI-LB.…”
Section: Discussionsupporting
confidence: 62%
See 4 more Smart Citations
“…Cardiac scintigraphy with MIBG is a biomarker for DLB 29 and in this cohort we recently reported that MIBG also had diagnostic accuracy in distinguishing MCI-LB from MCI-AD, 12 providing further evidence that autonomic nervous system involvement is present at the MCI stage. However, we did not find any clear association between cardiac denervation assessed with MIBG imaging and autonomic symptoms within MCI-LB.…”
Section: Discussionsupporting
confidence: 62%
“…Dopaminergic 123I‐N‐fluoropropyl‐2β‐carbomethoxy‐3β‐(4‐iodophenyl) single‐photon emission computed tomography (FP‐CIT) and cardiac MIBG imaging were carried out, as previously described 12,14 . FP‐CIT images were visually rated as normal or abnormal by a five‐person panel of experienced image analysts, blind to clinical information 14 .…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations